Multifunctional coatings for biomedical applications - Yigit, Oktay; Topuz, Mehmet; Dikici, Burak (CRC Press, 2025)
In recent years, there has been a growing interest in the development of multifunctional coatings for biomedical applications. These coatings have the potential to improve the biocompatibility, durability, and functionality of biomedical implant materials. Multifunctional coatings can provide a range of benefits, including enhanced biocompatibility, reduced infection rates, improved mechanical properties, and increased drug delivery capabilities. They can also be tailored to specific applications, such as antimicrobial coatings for implant surfaces or drug-eluting coatings for stents. There are many different types of materials that can be used to create multifunctional coatings, including polymers, ceramics, metals, and composites. The choice of material depends on the specific application and desired properties of the coating. Various techniques can be used to apply multifunctional coatings, including physical and chemical vapor deposition, electrospinning, sol-gel, or spray coating. These techniques can also be combined to create more complex coatings with multiple functions. Overall, the development of multifunctional coatings for biomedical applications is an exciting area of research that has the potential to significantly improve the performance and longevity of biomedical implant materials. © 2025 selection and editorial matter, Ajit Behera, Kuldeep K Saxena, Dipen Kumar Rajak and Shankar Sehgal. All rights reserved.